If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = 9x + 8 Reorder the terms: 2 + 3y = 9x + 8 Reorder the terms: 2 + 3y = 8 + 9x Solving 2 + 3y = 8 + 9x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3y = 8 + -2 + 9x Combine like terms: 2 + -2 = 0 0 + 3y = 8 + -2 + 9x 3y = 8 + -2 + 9x Combine like terms: 8 + -2 = 6 3y = 6 + 9x Divide each side by '3'. y = 2 + 3x Simplifying y = 2 + 3x
| 138-3x=33x+18 | | 9-7x=204-42x | | 5x+2+6=2x+28+x | | 3x-y+6x+7y= | | 15x+5=755 | | -5(b-7)-3b=-23 | | X+x^2=90 | | -5=2+w | | 2x+3x+4x= | | 11-9x=28-16x | | 8*(x-2)+16=7*(x+2) | | 3x+(-8)=-71 | | 3x-5x+x=10 | | 9x^2-2=0 | | 2x-4(x+2)=5x+6 | | 5x+6b=45 | | s=p+16 | | 4(3w-7)=32 | | x+1.1=8.1 | | -7u=-21 | | A+7.2=4 | | x+9.1=-6.9 | | (x-19)2=4 | | 4(5q-4)-[2(3q-3)+5]= | | x+-3=-1 | | (x-8)(x-8)=49 | | 8*(x-2)+16=6*(x-2) | | x^2+12=72 | | x-(-9.9)=2.1 | | 6-5(3x-3)=-39 | | x+7.1=3.9 | | 9x+56=16x+10 |